Analysis of Indoor Environmental Health Factors Related to the Incidence of Tuberculosis in Children in Jember District - batistha, zidni imanial; Novi M, Ancah Caesarina; Yusi R, Leersia; Yuhbaba, Zidni Nuris (Jurnal Kesehatan dr. Soebandi, 2025)
The environment of a house that is not clean can lead to the onset of diseases, including pulmonary TB. Environmental factors affecting TB incidence may include cleanliness of the house, ventilation, lighting, air temperature, humidity levels, and occupancy density. The purpose of this study was to analysis the relationship between indoor environmental health and the incidence of tuberculosis in children in Jember Regency. This research used an analytical observational study design with a case-control approach. The study included 68 TB-positive and 68 TB-negative respondents selected through simple random sampling. Statistical analysis involved bivariate tests such as chi-square and multivariate analysis using logistic regression. The findings revealed a significant relationship between environmental health and childhood tuberculosis incidence (p=0.030). Factors such as room temperature, humidity, ventilation, lighting, wall type, and occupancy density were identified as risk factors for childhood tuberculosis in Jember. The government is encouraged to support and empower local communities through mutual cooperation activities to create a healthier physical environment at home.